Quality Testing Assistance and Improvement of Production Facility Infrastructure for the Vigur Asri Women Farmers Group in Malang City (TEKAD : Teknik Mengabdi, 2025)
Efforts to improve the quality of Virgin Coconut Oil (VCO) products and enhance production facilities were carried out for the Vigur Asri Women Farmers Group (KWT) in Malang City. The main issue faced by the group was consumer complaints regarding rancid VCO products occurring before the expiration date. This problem was presumed to result from high moisture content and air contamination due to inadequate ventilation and hygiene in the production area. To address these issues, a community assistance program was implemented through training on moisture content testing based on the Indonesian National Standard (SNI 3781:2008) and the reorganization of the production room to improve air circulation. The testing process employed a simple, cost-effective method using an oven and an analytical balance, which was easy for participants to understand and apply. Activity evaluation focused on participants’ ability to follow testing procedures and comprehend product quality standards. The results showed that the VCO’s moisture content was successfully reduced to 0.2%, meeting the maximum limit required by SNI. Furthermore, the improvement of production facilities enhanced product quality and competitiveness. This program positively impacted the group’s capacity to produce high-quality VCO sustainably.